The Effect of TiO2 as a Photocatalytic Paint in The Indoor Air Purification Process - Ravan Allababidi (Journal of Ata-Chem)
Photocatalysis has applications in various fields, such as in air purification devices and even in coatings, where it can be incorporated into paint formulations to take advantage of its air purification and self-cleaning properties. This report looks not only at the process of photocatalysis, but also at studies that have been carried out on its incorporation into coatings using titanium dioxide (TiO2). TiO2 is commercially available and can be synthesized in the laboratory to improve its performance in air purification and decontamination of various pollutants. In addition, studies into enhancing TiO2 semiconductor materials with a photocatalytic system, such as the inclusion of manganese, were emphasized. These studies presented findings on boosted decontamination performance, which is critical for enhancing indoor air quality through the elimination of harmful gases and organic compounds. Volatile organic compounds, such as formaldehyde, toluene, benzene, and NOx, have extremely toxic health effects. Every year, indoor and outdoor air pollution causes a significant number of deaths. Considering that people spend more than 80% of their time indoors, the filtration of indoor air is even more important. Therefore, this article presents some studies on the further development of photocatalytic materials and technologies for the commercial application of photocatalytic paints. Commercial photocatalytic paints containing TiO2 doped with magnesium (Mn), silicate paints and water-based styrene acrylic paints were investigated, focusing on their ability to reduce VOC emissions.